Oxygen barrier properties of new thermoplastic natural rubber nanocomposites - Hassan, Noor Azlina; Ahmad, Sahrim; Rasid, Rozaidi; Abd Razak, Shamsul Bahri; Y. , Yamamoto; S. , Kawahara (Taylor & Francis, 2011)
Nanocomposites of linear low-density polyethylene (LLDPE)/ natural rubber (NR)/liquid natural rubber (LNR) blend denoted as TPNR with montmorillonite-based organoclay (OMMT) were prepared using melt blending method. The melt blending of LLDPE/NR/LNR with a composition of 70:20:10 formed blends. For better dispersion of nanoclay in the TPNR blend, MA-PE was used as a coupling agent. The nanoclay dispersion was investigated by X-ray diffraction (XRD), and a novel method using permeability measurements data in a permeability model. The measured dspacing data proved a good dispersion of nanoclay at low clay contents. The permeability model for flake-filled polymer was used to estimate the aspect ratio of nanoclay platelets in the blend nanocomposites. The oxygen barrier property of the TPNR blend improved about two-fold by adding only 2 wt% of organoclay. Differential scanning calorimetry showed an increase in crystallinity up to 20% suggesting an increase in spherulite growth, by the increased in melting temperature. The increase in the barrier property of the blend with the induction in crystallinity indicates the dominant role of organoclay platelets in barrier improvement. Scanning electron micrographs of tensile fracture surface of the nanocomposite, exhibited a very ductile surface indicating a good compatibility of LLDPE and NR and also, a possible contribution of nanoparticles to the deformation mechanism, such as extensive shear yielding in the polymer blend. The transmission electron micrograph, showed an intensive intercalation structure and exfoliation structure with the presence of MA-PE.